2011
DOI: 10.1007/s12017-010-8142-6
|View full text |Cite
|
Sign up to set email alerts
|

CALM, A Clathrin Assembly Protein, Influences Cell Surface GluR2 Abundance

Abstract: The clathrin assembly protein, CALM, promotes the assembly of clathrin-coated vesicles. In a previous study, we showed that CALM controls the level of the synaptic vesicle protein VAMP2 at the plasma membrane by regulating VAMP2 endocytosis. Here, we provide evidence that CALM also influences the cell surface level of the AMPA receptor subunit GluR2. Although mechanistic details as well as the physiological relevance of CALM and GluR2 in the neuron have yet to be established, CALM-mediated trafficking could fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
(22 reference statements)
0
20
0
Order By: Relevance
“…This same association has been replicated several times [78, 82, 83, 86, 87, 114]. PICALM is involved in protein trafficking and synaptic vesicle endocytosis and may control levels of GluR2 and VAMP2 [112, 115, 116]. Its main function, however, is as a clathrin assembly protein, where it increases clathrin-coated vesicle assembly and helps regulate the amount of membrane recycling and clathrin-mediated endocytosis [115, 117].…”
Section: Geneticsmentioning
confidence: 90%
“…This same association has been replicated several times [78, 82, 83, 86, 87, 114]. PICALM is involved in protein trafficking and synaptic vesicle endocytosis and may control levels of GluR2 and VAMP2 [112, 115, 116]. Its main function, however, is as a clathrin assembly protein, where it increases clathrin-coated vesicle assembly and helps regulate the amount of membrane recycling and clathrin-mediated endocytosis [115, 117].…”
Section: Geneticsmentioning
confidence: 90%
“…CALM has been shown to regulate the endocytosis of a subset of membrane proteins as its cargo 14,20,[35][36][37] . In regard to the recognition of the cargo, it has recently been shown that VAMP8, ARTICLE one of the R-SNARE proteins, binds directly to the C-terminal edge of ANTH domain and is internalized in a CALM-dependent manner 16 .…”
Section: Expression Level Of Calm Is Correlated With Ab42 Ratiomentioning
confidence: 99%
“…In addition to affecting SNAREs at the presynaptic membrane, PICALM has also been found to modulate the abundance of alpha-amino-3-hydroxy-5-methyl-4-isoaxolepropionate (AMPA) receptor subunit GluR2 at the postsynaptic membrane by influencing its endocytic trafficking [106]. Interestingly, GluR2 levels on the surface of the postsynaptic terminal are closely associated with the intensity of synaptic transmission [107].…”
Section: Picalm and Synaptic Function In Admentioning
confidence: 99%